Revaccination of recently processed cattle - M.F. Spire; Jack G. Riley; A.J. Edwards (Kansas Agricultural Experiment Station Research Reports, 1983)
Two trials were conducted to evaluate the effectiveness of revaccinating recently processed cattle with modified live IBR and BVD vaccine. Revaccination decreased total illness 24 to 26%. A significant reduction in clinically sick calves occurred by 48 hours after revaccination and continued for the reminder of the observation period.
Keywords: Cattlemen& #x27; s Day; 1983; Report of progress (Kansas State University. Agricultural Experiment Station); 427; Beef; Revaccination; IBR; BVD